2019
DOI: 10.1111/1744-7917.12691
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral evidence for contextual olfactory‐mediated avoidance of the ubiquitous phytopathogen Botrytis cinerea by Drosophila suzukii

Abstract: Herbivorous insects may benefit from avoiding the smell produced by phytopathogens infecting plant host tissue if the infected tissue reduces insect fitness. However, in many cases the same species of phytopathogen can also infect host plant tissues that do not directly affect herbivore fitness. Thus, insects may benefit from differentiating between pathogen odors emanating from food and nonfood tissues. This is based on the hypothesis that unnecessarily staying attentive to pathogen odor from nonfood tissue m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Previously, Graziosi and Rieske 36 had also shown that infection by Colletotrichum acutatum increases the mortality of the Asian chestnut gall wasp D. kuriphilus. Raspberries infected by the fungus B. cinerea also repelled D. suzukii and reduced larval survival and adult oviposition and size 11 . Interestingly, our results showed that both anthracnose solutions ('field' and 'colony'), but not the 'filtered' solution, have repellent and insecticidal effects on D. suzukii, indicating that removing C. fioriniae conidia eliminates these negative effects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, Graziosi and Rieske 36 had also shown that infection by Colletotrichum acutatum increases the mortality of the Asian chestnut gall wasp D. kuriphilus. Raspberries infected by the fungus B. cinerea also repelled D. suzukii and reduced larval survival and adult oviposition and size 11 . Interestingly, our results showed that both anthracnose solutions ('field' and 'colony'), but not the 'filtered' solution, have repellent and insecticidal effects on D. suzukii, indicating that removing C. fioriniae conidia eliminates these negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, fruit infection by fungal pathogens can also negatively affect Drosophila spp. For example, D. suzukii larval survival and adult size were significantly reduced when they were reared on raspberries infected by Botrytis cinerea Pers., and fruit infection by this fungus also reduced fly attraction and oviposition 11 . Therefore, odors from microbes associated with D. suzukii could serve as sources of attractive and repellent compounds to manipulate the fly's behavior in agroecosystems 17,18 .…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…16,21,22 While octenol is a common mushroom alcohol emitted by fungal fruiting bodies, geosmin is an earthy odor associated with soil dwelling fungi and bacteria, 21 and both are presumably deterrent due to the close association of these odors with potential pathogen infection. 23,24 Previous studies on these repellents have focused on product efficacy aimed at establishing the degree of deterrent action and relative dose responses. In the lab, octenol reduces oviposition in raspberries at concentrations as low as 0.1%, increasing in effect in preparations up to 10% v/v preparation in mineral oil.…”
Section: Introductionmentioning
confidence: 99%